Investigating the role of the anti-malarial drug Atovaquone in anti-cancer therapy - Watson, D; Coates, J (2019)
Radiotherapy (XRT) is used in over half of all cancer treatment regimens and can be administered alone or in tandem with chemotherapeutics to improve clinical outcomes. Sub-physiological levels of oxygen (hypoxia) is a feature of many solid tumours and can diminish the effectiveness of anti-cancer treatments. Though its detrimental impact on treatment efficacy was first realised over half a century ago, hypoxia endures as a significant barrier to improving clinical outcomes.